2018
DOI: 10.1002/jhet.3297
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bridgehead Thiadiazolopyrimidine Derivatives with Antimicrobial and Antitumor Activities

Abstract: Because of the remarkable pharmacodynamics and chemotherapeutics activities of thiadiazolopyrimidines, a new series of 1,3,4‐thiadiazolo[3,2‐a] pyrimidine derivatives have been synthesized by reacting 5‐substituted‐2‐aminothiadiazoles 1a,b with different reagents: active methylenic compounds, benzaldehyde under different conditions, isatin, and cyclic ketones. The structures of the novel compounds have been inferred by spectroscopic methods (infrared, 1H‐NMR, 13C‐NMR, and mass spectrometry) and elemental analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…34 Azab et al have reported a two-step method for 5H-1,3,4-thiadiazolo[3,2-a] pyrimidin-5-ones, which involved the reaction of 2-amino-1,3,4-thiadiazoles to ethyl cyanoacetate and tandem reduction and deamination in the presence of phosphorus pentoxideformic acid. 35 Zhao et al have described the synthesis of 5H- [1,3,4]thiadiazolo [3,2-a]pyrimidine-6-carboxylate derivatives using aldehydes, 2-amino-thiadiazole and acetoacetate by onepot MCR strategy under microwave irradiation. 36 The synthesis of anticancer compounds, 7-substituted-phenyl-8,8adihydro-7H- [1,3,4]thiadiazolo [3,2-a]pyrimidine-6-carbonitriles was achieved by Tiwari and co-workers from the one-pot reaction of 5-(4-chlorophenyl)-1,3,4-thiadiazol-2 amine, aromatic aldehydes and malononitrile under ultrasonic irradiation and NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…34 Azab et al have reported a two-step method for 5H-1,3,4-thiadiazolo[3,2-a] pyrimidin-5-ones, which involved the reaction of 2-amino-1,3,4-thiadiazoles to ethyl cyanoacetate and tandem reduction and deamination in the presence of phosphorus pentoxideformic acid. 35 Zhao et al have described the synthesis of 5H- [1,3,4]thiadiazolo [3,2-a]pyrimidine-6-carboxylate derivatives using aldehydes, 2-amino-thiadiazole and acetoacetate by onepot MCR strategy under microwave irradiation. 36 The synthesis of anticancer compounds, 7-substituted-phenyl-8,8adihydro-7H- [1,3,4]thiadiazolo [3,2-a]pyrimidine-6-carbonitriles was achieved by Tiwari and co-workers from the one-pot reaction of 5-(4-chlorophenyl)-1,3,4-thiadiazol-2 amine, aromatic aldehydes and malononitrile under ultrasonic irradiation and NaOH.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-component reactions are special types of synthetic organic strategies in which three or more reactants react to give a final product in one-pot procedure [1][2][3][4]. Pyrimidinones (Biginelli compounds) derivatives are of considerable interest, as they are a class of natural and synthetic compounds that possess a great variety of biological and pharmaceutical activities [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Amino-4-(4-chlorophenyl)-5-oxo-4H,5H-pyrano[2,3-d] pyrido[1,2-a] pyrimidine-3-carbonitrile(2). Anal.…”
mentioning
confidence: 99%
“…From biological aspects, previous studies have reported that quinazolinone derivatives exhibited a pharmacological properties such as antitumor [13], anti-inflammatory [14][15][16], anticonvulsant [17,18], anti-HIV [19,20], antihypertensive [21][22][23], diuretic agent [24], antitubercular [25], antibacterial [26][27][28][29], and antitumor activities [29][30][31]. As a result of the aforementioned facts and in continuation for our program in the synthesis of biologically active heterocyclic systems [32][33][34][35][36][37][38][39], 2-pentylbenzoxazin-4-one 1 and 3-amino-2-pentylquinazolin-4-one 6 were used as a versatile key staring for the synthesis of novel heterocyclic compounds. The structure of the newly synthesized compounds were elucidated from elemental analyses and different spectroscopic data (infrared [IR], 1 H-NMR, 13 C-NMR, and mass spectrometry [MS]).…”
Section: Introductionmentioning
confidence: 99%